If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x) + 90 = 48 Reorder the terms: 90 + (2x) = 48 Solving 90 + (2x) = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + (2x) = 48 + -90 Combine like terms: 90 + -90 = 0 0 + (2x) = 48 + -90 (2x) = 48 + -90 Combine like terms: 48 + -90 = -42 (2x) = -42 Divide each side by '2'. x = -21 Simplifying x = -21
| -1.5=-6/x | | 2x-22=x+3 | | 6(6v+7)-5=1+6v | | 9a-2(3a-6)=12 | | -7x+15x^2=20x | | 207=47x+-28 | | 12n=11n/19 | | 44=-6+m | | 52=x(1-x)x | | (5x-6)(2-x)=0 | | 52=x(1-x)+x | | 52=x(1-x) | | 6x+6=35x-30 | | 3x^2+28x-6=0 | | -2(1-x)-11=5 | | b-4=28 | | x/35=-25-22 | | 7(12)+6y=42 | | 7(9)+6y=42 | | 5-3x=3+4x | | 3*t=21 | | 5-3/x=7/2x | | 5x=4-3/x | | 7x+6(0)=42 | | 7(0)+6y=42 | | a=(1.7)/6*s | | -1x-209=-3548 | | 35x=-25-22 | | 7(0)+6y=54 | | 1x+209=3548 | | -8m-10=82 | | (8a+60)+7=-13 |